2012
DOI: 10.1063/1.4733340
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of glass-forming ability of Fe-based bulk metallic glasses with high saturation magnetic flux density

Abstract: The effects of substituting Fe with Ni on thermal properties, glass-forming ability (GFA) and magnetic properties of Fe76-xNixMo3.5P10C4B4Si2.5 (x = 0−30 at.%) alloys were investigated in detail. The breadth of the supercooled liquid region was found to gradually increase from 42 to 55 K with increasing Ni content to 30 at.%. When x = 5 at.%, the alloy composition approached a eutectic point, resulting in an increase in GFA. As a result, FeNiMoPCBSi bulk metallic glasses with critical diameters up to 5.5 mm we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…[9][10][11] Fe-based BMGs display a unique magnetic property, so it is oen used in coil production. [12][13][14] In addition, Fe-based BMGs also have excellent corrosion resistance, allowing for their placement in the body as a biomedical implant material, of which 316L stainless steel, Ti-based BMG, and Co-Cr alloys are commonly used. Although those medical alloys are similar, studies have shown that 316L stainless steel is potentially harmful to the human body because its components contain nickel (Ni), which easily reacts to produce nickel ions aer corroding.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Fe-based BMGs display a unique magnetic property, so it is oen used in coil production. [12][13][14] In addition, Fe-based BMGs also have excellent corrosion resistance, allowing for their placement in the body as a biomedical implant material, of which 316L stainless steel, Ti-based BMG, and Co-Cr alloys are commonly used. Although those medical alloys are similar, studies have shown that 316L stainless steel is potentially harmful to the human body because its components contain nickel (Ni), which easily reacts to produce nickel ions aer corroding.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Pd-Si alloys, typical ideal systems for studying amorphous structures and properties, were always attracted for theoretical research and simulations. As a binary alloy system, the maximum casting thickness is 8mm, which is even bigger than some ternary alloys.…”
Section: Introductionmentioning
confidence: 99%
“…9 Pd-Cu-Si, one of the first bulk metallic glasses developed in 1974 by Chen et al, was often selected for scientific investigation in the common composition Pd 77.5 Cu 6 Si 16.5 , 10-13 but systematic study on the effect of different Cu addition on the glass formation is still limited. In this case, the binary alloy series Pd 81+x Si 19-x (x=0, 1, 1.5, 2, 2.5, 3, 4) and the ternary alloy series Pd 83.5-x Cu x Si 16.5 (x=0, 2,4,6,8,10,12) were selected to investigate the effect of Cu additions on the glass forming ability (GFA) and thermal stability in the binary Pd-Si system. First, a combination of X-ray diffraction (XRD), transmission electronic microscopy (TEM) and differential scanning calorimetry (DSC) was used to investigate the amorphous state of the produced samples.…”
Section: Introductionmentioning
confidence: 99%
“…However, these Fe-based metallic glasses have the limitation of a reduced critical diameter, few millimeters when produced as bulk amorphous alloys, because of their low GFA. Therefore, there is a limitation for the potential use of Fe-based metallic glasses in engineering applications and, nowadays their production is mostly in form of thin ribbons, wires and films [6]. The first Fe-based bulk metallic glass, Fe-(Al,Ga)-(P,C,B,Ge,Si), was produced in a shape of a rod with 1-2 mm diameter in 1995 [7].…”
Section: Metallic Glassesmentioning
confidence: 99%